Medieval commentaries on Aristotle's Categories - Newton, Lloyd A. (Brill's companions to the Christian tradition ;, 2008)
Covers a range of philosophers, from Simplicius to John Wyclif, and philosophical problems, including: the harmony of Platonism and Aristotelianism; the relationship between logic, and metaphysics; the number of categories; and realism versus nominalism.